Pengaruh Substitusi Tepung Labu Kuning (Cucurbhita Moschata)Terhadap Kadar Β-Karoten dan Daya Terima Pada Biskuit Labu Kuning - Widyastuti, Anggraini Dewi; , Eni Purwani, S.Si., M.Si; , Pramudya Kurnia, STP, M.Agr (2015)
Background: Beta carotene very needed by the body to prevent a deficiency of vitamin a (DVA). One of alternatives that can be taken to reduce the occurrence of vitamin a deficiency is by means various kind of Food based local food source of vitamin a. Various kind of food can be done by making food products such as biscuit yellow squash. Objective: Knowing the substitution of yellow squash against levels of beta carotene and resources on biscuits yellow squash Research Method: According to this research its kind is research experiment. Research design used is random design complete with four variations of the substitution of flour treatment yellow squash. Testing levels of beta carotene done by means of the spectrophotometer test. Received the resources obtained through organoleptik testing conducted by the panel somewhat trained as many as 25 people that is a student of nutrition muhammadiyah university surakarta. The beta carotene test analyzed using anova one direction with significant level of 95% (α= 0,05) and Resources test analyzed using friedman test with significant level of 95 % (α= 0,05). Result: The results of research shows that based on the levels of beta carotene , obtained the highest levels of beta carotene is on a biscuit with the substitution of flour is 15% of yellow squash 13,349 µg/100 gram. Of statistical tests annova on the substitution of flour yellow squash against levels of beta carotene indicate its value of p = 0,000. Statistical testing shows power color received against the value of p = 0,001; the scent of the value of p = 0,000; taste the value of p = 0.008; texture the value of p = 0,055; and preferences a whole by the value of p = 0,000. Conclusion: There's an effect which is significant at the substitution of flour yellow squash against levels of beta carotene and there is the influence of the substitution of flour yellow squash in making biscuits yellow squash received on power which includes Color, the scent of, a sense of, and preferences a whole and there are no flour the influence of the substitution of yellow squash in making biscuits yellow squash power to receive from the perspective of texture.